New species of Archimonocelididae Meixner, 1938 (Platyhelminthes, Proseriata) from the Pacific Ocean, with the proposal of three new genera - Schockaert, Ernest R.; Curini-Galletti, Marco (Zootaxa, 2025)
The genera Karlingocelis gen. nov., Martensocelis gen. nov., and Australocelis gen. nov. are introduced for species of Archimonocelididae (Proseriata) characterized by unique features of their sclerotised structures. Species of Karlingocelis gen. nov. possess a short stylet surrounded distally by paired hooks, sitting on strong muscles. Three species from the Pacific are ascribed to the new genus, two of which are new: they may be distinguished by the morphology of their copulatory structures. K. karlingi sp. nov. (type species of the new genus) from Australia (Heron Island) has a stylet 110–120 µm long, with one pair of hooks about 60 µm long. The stylet of K. helfrichi (Karling, Mack-Fira and Dorjes, 1972) comb. nov. from the Hawai’i Islands is 54–60 µm long, and is surrounded by two pairs of hooks, about 12 µm long; K. cannoni sp. nov. from Australia (Heron Island) has a stylet about 70 µm long, and four pairs of hooks about 25 µm long. The three species have very similar karyotypes, with n=5, and evenly sized chromosomes. Species of Martensocelis gen. nov. have a C-shaped prostate vesicle and a recurve, narrowly tubular stylet with a wide proximal funnel-like opening and surrounded distally by short needles. The type species M. martensi sp. nov., from New South Wales, has multiple pharynges and a stylet 150–175 µm long, distally surrounded by a girdle of 30–40 needles, ranging in length 50–80 µm. All other species have a single pharynx. M. justinei sp. nov., from New Caledonia, has a stylet 215–230 µm long, and four straight needles 50–55 µm long. M. coffsia sp. nov., from New South Wales, has a stylet 85 µm long, and 10 needles 20–25 µm long, while M. aquilae sp. nov., from Tasmania, has a stylet 95 µm long, less recurve than the other species, and about 10 spines, most of which have very poorly sclerified stalks. M. piscatoris sp. nov., from New South Wales, has a stylet curved to over 180° and 185 µm long, with nine accompanying needles, 75–80 µm long, very slender and with sharp distal tips, and is further provided with two additional needles, about 90 µm long, running from the base of the stylet almost to its distal tip. Species of Australocelis gen. nov. have a straight stylet, and the accompanying needles are symmetrically arranged at either side of the stylet, in groups of different morphology. The type species, A. newmanae sp. nov., from South Australia, has a stylet 70 µm long, and eight needles arranged into two groups; A. rhizophoralis (Martens & Curini-Galletti, 1989) comb. nov., from northern Australia (Darwin, Northern Territory) has a stylet 65 µm long, and 12 needles, arranged into three groups.